Three new diterpenoids from Euphorbia peplus. Issue 21 (2nd November 2021) - Chen, Yan-Ni; Lu, Qing-Yun; Li, Dong-Mei; Li, Ying-Yao; Pu, Xue-Xue; Li, Bo-Ting; Tang, Xiao-Han; Tang, Hong-Yu; Liu, Shuai; Yang, Lei; Zhang, Yu; Di, Ying-Tong; et al.
Abstract: Three new diterpenoids (1–3 ) (two abietane type diterpenoids and a paralianone type diterpenoid), together with four known compounds (4–7 ) were isolated from the whole plants of Euphorbia peplus . Their structures were elucidated through spectroscopic analysis and physicochemical characteristics. The cytotoxic activities of compounds 1–7 against five human tumour cell lines were evaluated, however, they were inactive at the concentration of 40 μM. The compound 3 enhanced lysosomal biogenesis with Lyso Tracker staining intensity of 132.6%. Graphical Abstract: